2022
DOI: 10.3390/buildings12060741
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Message Frame and Reference Point on Recycled Water Acceptance in Green Community: Evidence from an Eye-Tracking Experiment

Abstract: Public rejection of recycled water hinders the application of recycled water use projects in green communities. An effective information outreach strategy could help to overcome this obstacle. This study used message frames and reference points as control variables to design experimental materials and conduct eye-movement experiments to determine the effect of different information promotion strategies. The results of the study show that: (1) compared with the loss frame, the gain-framed messages are more effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 90 publications
0
2
0
1
Order By: Relevance
“…Research shows that information focus can have an impact on attitudes and behaviors [ 41 ]. Fu et al demonstrated through an eye-tracking experiment that the reference point and the message frame have an interactive effect on the visual cognition of advertisements for the use of recycled water in green communities, and the reference point has a moderating impact on the message frame [ 42 ]. Lu et al examined the effectiveness of consistently matching reference points and the message frame in intervening in risk perception and behavioral intention construction in human–black bear conflicts [ 43 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research shows that information focus can have an impact on attitudes and behaviors [ 41 ]. Fu et al demonstrated through an eye-tracking experiment that the reference point and the message frame have an interactive effect on the visual cognition of advertisements for the use of recycled water in green communities, and the reference point has a moderating impact on the message frame [ 42 ]. Lu et al examined the effectiveness of consistently matching reference points and the message frame in intervening in risk perception and behavioral intention construction in human–black bear conflicts [ 43 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Secondly, in terms of safety management, the improvement of construction workers' safety attitude is the only way the development of safety management. Therefore, the construction party should pay attention to the important role of personal safety attitude in safety management, and actively use the institutional environment and other organizational resources to jointly promote the improvement of personal safety attitude (such as VR accident experience and eye-tracking study), so as to realize safety management and intelligent implementation and also promote the transformation and upgrading of the traditional construction industry [42]. Finally, the construction party should actively build the safety culture of the project, and create a positive safety culture which is the embodiment of effective safety communication among team members, and then affect the safety atmosphere of the team, and correct the unsafe attitude of construction workers, so that safe construction in the project becomes a normal state.…”
Section: Research Conclusion and Implicationsmentioning
confidence: 99%
“…Outo estudo interessante que utilizou o rastreamento ocular, verificou a aceitação de água reciclada, no qual foram expostas mensagens textuais nas opções de escolhas dos consumidores. Interessantemente, foi possível observar que mensagens que promoviam um ganho para a comunidade tiveram maior aceitação do que as mensagens que eram estruturadas promovendo a perda de determinado benefício (Fu et al, 2022).…”
Section: Iso 14025unclassified